Religious division and social conflict : the emergence of Hindu n ationalism in rural India - Froerer, Peggy (New Delhi : Social Science Press : Hyderabad : Distributed by Orient Longman, 2007)
Study based on Oraons, Indic people; with reference to Mohanpur, a v illage in Korba District, India.
Originally presented as the author's thesis (Ph. D.)--London School of Economics, 2002.
Includes bibliographical references (p. [267]-287) and index.
Keywords: Oraon (Indic people) -- India -- Mohanpur -- Religion; Social conflict - Abstracting and indexing -- - Great Lakes region; Hindutva -- India -- Mohanpur; Nationalism -- Religious aspects -- Hinduism; Mohanpur (India) -- Religion